KPI measurement framework for the Malaysian construction project / Nazipah Ab. Rahman - Ab. Rahman, Nazipah (2011)
Most industries are aware of the existence of KPI measures to measure performance. However, for traditional businesses, performance is still measured solely in financial terms. The increasing number of project failures nowadays will encourage the organization to recognize the value and the importance of project measures. Therefore there is a great need for the Malaysian construction industry to identify an effective and realistic KPI framework to measure project performance to ensure continuous improvement and successful delivery of projects. The focus of this research is to develop an effective KPI measurement framework that will enable contractors to determine the standard of their projects and to review them so that measures can be taken to improve performance and project delivery. Empirical research was undertaken by means of questionnaire surveys which were administered to the Class G7 of Malaysian contractors, resulting in a total of 60 valid responses returned. Further statistical analysis of the collected survey responses provided information on the identification of perceived KPIs and displayed realistic parameters as well as the contractors' understanding of performance measures. In this study, the results were analysed by means of various statistical methods through the statistical analysis software, SPSS 17. The findings from the research and the questionnaires were then used in the development of a KPI framework model. In order to underpin the framework developed, functionality trials were conducted with six case studies by using the data from completed projects in the formulated framework to obtain quantifiable results. The findings from the research resulted in the development of the KPI Measurement Framework model for the contractors to determine and assess the standard of project performance. This framework is the lagging measures of the project and can be easily used to improve the performance of other projects. The six KPIs (time, cost, quality, productivity, customer satisfaction and safety and health) identified in the framework were used to assess the level of project performance.